Feed addition of curcumin to laying hens showed anticoccidial effect, and improved egg quality and animal health - Galli G.M.* (2018)
© 2018 Elsevier LtdThe aim of this study was to evaluate whether the addition of curcumin in the diet of commercial laying hens could have an anticoccidial action and improve egg quality. For this, 60 laying hens were divided into three groups: T0 (the control group); T30 and T50 (30 and 50 mg/kg of curcumin in the feed, respectively). Eggs recently laid were collected on days 14 and 21 of the experiment, and stored for 21 days. It was observed increased specific gravity and yolk index in stored eggs of the groups T30 and T50 compared to T0. The yolk color reduced in the eggs stored from groups T30 and T50 compared to T0. Moreover, TBARS levels were lower in fresh and stored eggs from groups T30 and T50. It was observed increased TAC levels in fresh eggs from groups T30 and T50 and in stored eggs from the group T50. The presence of curcumin was not detected by HPLC in the yolk and albumen. Seric levels of albumin and uric acid did not differ between groups, while seric levels of total proteins increased on day 21 on groups T30 and T50. Finally, it was observed a significant reduction on the number of oocysts in fecal samples on days 14 and 21 of T30 and T50 compared to T0. Based on these evidences, it is possible to conclude that the addition of curcumin in the diet of laying hens has an anticoccidial effect and improves egg quality.